Article RETRACTED due to manipulation by the authors and citationsCoach-athlete emotional relationships in football and their impact on achievement motivation - Sulistiyo Sulistiyo; Hendra Setyawan; Nawan Primasoni; Widiyanto Widiyanto; Muhammad Soleh Fudin; Sabariah Sabariah; Rufi’i Rufi’i; Nuridin Widya Pranoto; Satria Yudi Gontara; Wilasari Arien; Susanto Susanto; Deasy Wahyuni; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Using the systematic literature review, this study investigates the emotional relationships between coaches and athletes in soccer and their impact on achievement motivation. Data were obtained from articles searched through Google Scholar. The search focused on the following keywords: "Emotional Relationship AND Coach AND Athlete AND Soccer AND Achievement Motivation". During the search, inclusion and exclusion criteria were applied. For example, the selected articles must be published in Scopus-indexed journals between 2019 and 2024. With these criteria, 17,300 articles were found. They were screened again in several stages, and 16 articles that fit the theme and met the inclusion requirements were chosen. During the article selection, this study followed the PRISMA guidelines, generating several key findings. The first finding of this study confirmed that emotional relationships between coaches and athletes in soccer are important in influencing motivation. A positive relationship, characterized by trust, emotional support, and effective communication, creates a conducive environment for athletes to develop intrinsic and extrinsic motivation, which ultimately impacts their performance on the field. Another finding revealed that a coach's emotional intelligence is a crucial factor in building such relationships, as the coach's ability to understand and respond to athletes' emotional needs can increase athletes' self-efficacy and intrinsic motivation, which in turn strengthens performance. Effective communication was also identified as a key element that enables coaches to provide constructive feedback and establish open channels of communication, thereby creating a climate that supports the development of athletes' achievement motivation.